SCANNING ELECTRON MICROSCOPIC OBSERVATIONS ON THE ANTENNA, LEG AND PROBOSCIS OF DROSOPHILA ANANASSAE - CHAKRABARTI, C.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
Some organs of adult Drosophia such as antennae, legs and proboscis are morphologically very distinct but genetically they are very close. All these structures are controlled by common homeobox gene. Homeotic mutations can transform one part of the adult body into another. In these experiments attempts were made to compare these structures at the ultramicroscopic level. Scanning electron microscopic observation on the antennae, legs and proboscis could not establish any homology among these structures besides the sensory hairs associated with the apical parts of the antennae, legs and proboscis which exhibit similarities to a great extent possibly, due to their common genetic origin.